Salinity (NaCl), Waterlogging, and their Combined Effects on Germination and Seedling Growth of Four Turfgrass Species. Issue 1 (26th February 2013) - Zhang, Qi; Zuk, Alan J.; Rue, Kevin
Abstract : Salinity and waterlogging are two major abiotic stressors commonly associated with irrigated soils. In this experiment, tall fescue cv. Stonewall, Kentucky bluegrass cv. Bewitched, blue grama ecotype Bad River, and buffalograss cv. Texoka were germinated under well‐drained (control), waterlogging (i.e., flooding), saline (5 g NaCl/liter), or a combination of waterlogging and saline conditions (saline‐waterlogging) in two greenhouses (Study I and II). Plants were evaluated on germination percentage, shoot and root fresh weight, and the longest root length. Waterlogging with tap water did not inhibit seed germination or seedling growth. Germination, shoot and root fresh weight, and the longest root length were significantly decreased under saline conditions, alone or combined with waterlogging. The highest reduction occurred under saline condition alone which ranged from 36% of the control in the longest root length in Study I to 1% of the control in root fresh weight in Study II. Soil salinity levels were similar between the control and waterlogging treatments, which was significantly lower than the salinity treatment and the combined effects. Tall fescue was the most tolerant to both salinity and waterlogging stresses. Kentucky bluegrass, blue grama, and buffalograss showed a similar level of tolerance to salinity, waterlogging, and the combined stress.